Stake Model Analysis on Islamic Boarding School Policy in Madura in Formation of Santri Attitudes towards Clean and Healthy Living - Thoriq Aziz Jayana; Abd Mukhid; Syafi'e Syafi'e; Sahrawi Sahrawi; Muhammad Nur Faiz (At-Ta'dib, 2022)
building a clean and healthy living culture should be an inseparable part of the pesantren. But in reality, the spread of skin diseases among students and the neglect of students in maintaining cleanliness have become a separate phenomenon. To solve these problems, an analysis of the pesantren's policies is needed, both related to aspects of taharah education/learning, as well as aspects of optimizing facilities and infrastructure in supporting the implementation of clean and healthy living. This research is a case study research, with an analytical-descriptive approach. The analytical method used is the evaluation of Stake model (countenance). Collecting data using interviews, observation, and documentation. The results of this study indicate that: 1) it is necessary to develop methods in teaching, especially in taharah material with a contextual learning approach (CTL) and problem-based (PBL). 2) the pesantren needs to optimize the infrastructure to support the implementation of clean and healthy living, such as empowering the poskestren, providing baths and clean water, regulating dormitory management so as not to overcapacity, etc.